Behavioral Attenuation - Benjamin Enke; Thomas Graeber; Ryan Oprea; Jeffrey Yang (CESifo GmbH, 2024)
We report a large-scale examination of behavioral attenuation: due to information-processing constraints, the elasticity of people's decisions with respect to economic fundamentals is generally too small. We implement more than 30 experiments, 20 of which were crowd-sourced from leading experts. These experiments cover a broad range of economic decisions, from choice and valuation to belief formation, from strategic games to generic optimization problems, involving investment, savings, effort supply, product demand, taxes, environmental externalities, fairness, cooperation, beauty contests, information disclosure, search, policy evaluation, memory, forecasting and inference. In 93% of our experiments, the elasticity of decisions to fundamentals decreases in participants' cognitive uncertainty, our measure of the severity of information-processing constraints. Moreover, in decision problems with objective solutions, we observe elasticities that are universally smaller than is optimal. Many widely-studied decision anomalies represent special cases of behavioural attenuation. We discuss both its limits and why it often gives rise to the classic phenomenon of diminishing sensitivity.
Keywords: 330; Verhalten; Verhaltensökonomik